Multicentre prospective observational study protocol for radiation exposure from gastrointestinal fluoroscopic procedures (REX-GI study). Issue 2 (26th February 2020) - Nishida, Tsutomu; Hayashi, Shiro; Takenaka, Mamoru; Hosono, Makoto; Kogure, Hirofumi; Hasatani, Kenkei; Yamaguchi, Shinjiro; Maruyama, Hirotsugu; Doyama, Hisashi; Ihara, Hideyuki; Yoshio, Toshiyuki; Nagaike, Koji; et al.
Abstract : Introduction: Recently, the use of various endoscopic procedures under X-ray fluoroscopic guidance, such as endoscopic retrograde cholangiopancreatography (ERCP), interventional endoscopic ultrasonography (EUS), enteral endoscopy and stenting, has been rapidly increasing because of the minimally invasive nature of these procedures compared with that of surgical intervention. With the spread of CT and fluoroscopic interventions, including endoscopic procedures under X-ray guidance, high levels of radiation exposure (RE) from medical imaging have led to major concerns throughout society. However, information about RE related to these image-guided procedures in gastrointestinal endoscopy is scarce, and the RE reference levels have not been established. The aim of this study is to prospectively collect the actual RE dose and to help establish diagnostic reference levels (DRLs) in the field of gastroenterology in Japan. Methods and analysis: This is a multicentre, prospective observational study that is being conducted to collect the actual RE from treatments and diagnostic procedures, including ERCP, interventional EUS, balloon-assisted enteroscopy, enteral metallic stent placement and enteral tube placement. We will measure the total fluoroscopy time (min), the total dose–area product (Gycm 2 ) and air-kerma (mGy) of those procedures. Because we are collecting the actual RE data and identifying the influential factors through a prospective, nationwide design, this study will provide guidance regarding the DRLs of ERCP, interventional EUS, balloon-assisted enteroscopy, enteral metallic stent placement and enteral tube placement. Ethics and dissemination: Approval was obtained from the Institutional Review Board of Toyonaka Municipal Hospital (25 April 2019). The need for informed consent will be waived via the opt-out method of each hospital website. Trial registration number: The UMIN Clinical Trials Registry, UMIN000036525.